1999
DOI: 10.1021/ma990197j
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Alignment of Polymer Liquid Crystals Containing Azobenzene Moieties in the Side Chain. 5. Effect of the Azo Contents on Alignment Behavior and Enhanced Response

Abstract: A series of side-chain polymer liquid crystals (PLCs) of 6-[4-(4-ethylphenyl)diazenylphenyloxy]hexyl methacrylate and 4′-[6-(methacryloyloxy)hexyloxy]-4-cyanobiphenyl were synthesized and characterized. The effects of contents of the azo units and the wavelength of irradiation light on photoinduced alignment behavior were investigated. On irradiation of linearly polarized light (LPL) at 366 nm directly, alignment change was induced only in the PLC with 6 mol % azo units (P6), while phase transition took place … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
78
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 36 publications
0
78
1
Order By: Relevance
“…It has been reported that visible light in the range of 436 to 514 nm can induce photoisomerizations in azobenzene. It has to be noted, however, that the amount of cis-azobenzene produced by visible light is much lower than that produced by UV light (e.g., 360 nm) [17]. In our case, irradiation at 420-nm laser light induces trans-to-cis and cis-to-trans photoisomerization cycles, followed by reorientation of azobenzene moieties.…”
Section: © 2001 Iupac Pure and Applied Chemistry 73 435-441contrasting
confidence: 51%
“…It has been reported that visible light in the range of 436 to 514 nm can induce photoisomerizations in azobenzene. It has to be noted, however, that the amount of cis-azobenzene produced by visible light is much lower than that produced by UV light (e.g., 360 nm) [17]. In our case, irradiation at 420-nm laser light induces trans-to-cis and cis-to-trans photoisomerization cycles, followed by reorientation of azobenzene moieties.…”
Section: © 2001 Iupac Pure and Applied Chemistry 73 435-441contrasting
confidence: 51%
“…[3][4][5][6] Such materials have a large induced birefringence, optical anisotropy and high writing-erasing rate.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular orientation in the polymer films can be quantitatively characterized by the birefringence measurement, polarized UV-Vis spectroscopy, and polarized IR spectroscopy [14,15,24,25]. In past decades, the correlation between the photoinduced orientation and molecular structures has been extensively studied for both liquid crystal azo polymers [12,13,[29][30][31][32][33], and amorphous azo polymers [16][17][18][19][20][21][22][23][24]. Understanding of the structure-property relationships has been used to elucidate the mechanism and develop materials with better performance.…”
Section: Introductionmentioning
confidence: 99%